Vaccination Coverage among Prisoners: A Systematic Review - Vicente-Alcalde, Nancy (Int J Environ Res Public Health, 2020)
Prison inmates are highly susceptible for several infectious diseases, including vaccine-preventable diseases. We conducted a systematic international literature review on vaccination coverage against hepatitis B virus (HBV), hepatitis A virus (HAV), combined HAV/HBV, tetanus-diphtheria, influenza, pneumococcal, and combined measles, mumps, and rubella (MMR) in prison inmates, according to the PRISMA guidelines. The electronic databases were used Web of Science, MEDLINE, Scopus, and Cinhal. No language or time limit were applied to the search. We defined vaccination coverage as the proportion of vaccinated prisoners. There were no limitations in the search strategy regarding time period or language. Of 1079 identified studies, 28 studies were included in the review. In total, 21 reported on HBV vaccine coverage (range between 16–82%); three on HAV (range between 91–96%); two studies on combined HAV/HBV (77% in the second dose and 58% in the third); three studies on influenza vaccine (range between 36–46%), one of pneumococcal vaccine coverage (12%), and one on MMR coverage (74%). We found that data on vaccination coverage in prison inmates are scarce, heterogeneous, and do not include all relevant vaccines for this group. Current published literature indicate that prison inmates are under-immunized, particularly against HBV, influenza, MMR, and pneumococci. Strengthen immunization programs specifically for this population at risk and improvement of data record systems may contribute to better health care in prisoners.